PEMETAAN RISET EMPIRIS : KASUS ADOPSI E-BANKING* - Edy Purwo Saputro; Fereshti Nurdiana Dihan (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
Diversity in the e-banking research models indicates that a behavioral research tends to be developing. Inaddition, that in the e-banking adoption research models, included in observation setting, shows that the ebankingadoption research is a very interesting phenomenon so that the conclusions, implications andlimitations of the previous researches give a chance to carry out further researches suitable to different andunique observation setting.The first year research orients to the examination and map of an e-banking adoption and the second oneexplores and exploits potency for building intention to use in the e-banking as effort to develop and grow a selfindependentbanking customer and develop all the potencies in relation to customers into a smart customer.Referring to the diversity in the e-banking research models, the map result is limited to the amount of journals(50 titles). When the journals can be reduced with the diversity in the models and cases in various countries, theimplication to the generalization has not been satisfactory. However, these journals are representative todetermine a model for building observation setting suitable to a research, included in making questionnaires.Based on the description above and limitation to empirical journals in number as a reference to map, it issuggested that a further research needs to add more journals, particularly to develop the findings of usedmodels and approach as well as method.